Multi-trait selection for drought-tolerant soybean accessions under contrasting water regimes - Tenena Silue; Bunmi Olasanmi; Adeyinka Saburi Adewumi; Paterne Angelot Agre; Idris Ishola Adejumobi; Paul Olabode Kehinde; Godfree Chigeza; Abush Tesfaye Abebe (PLoS ONE, 2026)
Soybean, a crucial source of protein and oil, faces significant yield reductions due to water stress, particularly at the flowering and pod-filling stages. This study evaluated 150 accessions from the Soybean Breeding Program of the International Institute of Tropical Agriculture (IITA) in Ibadan, Nigeria, under both well-watered and water-stressed conditions across two growing seasons using a multi-trait selection. Intermittent water stress was imposed at critical reproductive stages (35 and 63 DAS).Significant genetic variation (p < 0.001) was observed for all traits under bothwater regimes.Broad-sense heritability estimates ranged from 21.56% to 86.56%, with the highest values observed for lodging score and days to 50% flowering.. Grain yield under stress correlated positively with yield in non-stress conditions (r = 0.38), while hundred-seed weight showed consistent positive associations with yield across water regimes. The multi-trait genotype-ideotype distance index (MGIDI) identified 30 superior accessions under each water regime, with eight consistently outstanding across both. Drought tolerance indices further supported the identification of high-yielding, resilient genotypes, with SY150 emerging as the most stable across all three selection approaches. These findings demonstrate that integrating MGIDI with drought tolerance indices provides a powerful approach for simultaneous selection of yield potential and stress resilience. The identified accessions represent promising candidates advancing water-deficit-tolerant soybean breeding in sub-Saharan Africa.